On the Dark Side of Therapies with Immunoglobulin Concentrates: The Adverse Events - Späth, Peter J.; Granata, Guido; La Marra, Fabiola; Kuijpers, Taco W.; Quinti, Isabella (Frontiers in Immunology, 2015)
Abstract to the dark side of therapies with human immunoglobulin G concentrates Therapy by human immunoglobulin G (IgG) concentrates is a success story ongoing for decades with an ever increasing demand for this plasma product. The success of IgG concentrates on a clinical level is documented by the slowly increasing number of registered indication and the more rapid increase of the off-label uses, a topic dealt with in another contribution to this special issue of Frontiers in Immunology. A part of the success is the adverse event (AE) profile of IgG concentrates which, even at life-long need for therapy, is excellent. Transmission of pathogens in the last decade could be entirely controlled through the antecedent introduction by authorities of a regulatory network and installing quality standards by the plasma fractionation industry. The cornerstone of the regulatory network is current Good Manufacturing practice. Non-infectious AEs occur rarely and mainly are mild to moderate. However, in recent times the increase in frequency of hemolytic and thrombotic AEs raised worrying questions on the possible background for these AEs. Below we review elements of non-infectious AEs , and particularly focus on hemolysis and thrombosis. We discuss how the introduction of plasma fractionation by ion-exchange chromatography and polishing by immunoaffinity chromatographic steps might alter repertoire of specificities and influence AE profiles and efficacy of IgG concentrates.